Formation of a stable carbon framework in a MnO yolk–shell sphere to achieve exceptional performance for a Li-ion battery anode1. Issue 30 (14th August 2015) - Wang, Shengbin; Xiao, Changlei; Xing, Yalan; Xu, Huaizhe; Zhang, Shichao
<x xml:space="preserve">Abstract</x> A 3D carbon framework has been introduced into a MnO yolk–shell structure, which improves the reaction kinetics, prevents MnO from fracturing and agglomerating, and limits most SEI formation to the carbon surface instead of on the MnO–electrolyte interface.